SELF MICRO EMULSIFYING DRUG DELIVERY SYSTEM FOR IMPROVED ORAL DELIVERY OF LIPOPHILIC DRUGS - JILL B. SHUKLA (International Journal of Pharma and Bio Sciences, 2016)
Oral route has always been preferred route for formulators and has dominated over other routes of administrations. This route is limited to those drugs molecule that are permeable across the gastric mucosa and are at least sparingly soluble. Approximately 40% of new chemical entities exhibit poor aqueous solubility and present a major challenge to modern drug delivery system, because of their low bioavailability. Some examples of marketed lipid based formulations are Sand immune Neoral (Cyclosporine A), Novartis Pvt. Ltd. and Fortovase (Saquinavir), Roche Laboratories Inc. with much attention focused on self micro-emulsifying drug delivery systems (SMEDDS). Self microemulsifying drug delivery systems are isotropic mixtures of oil, surfactant, co-surfactant and drug with a unique ability to form fine oil in water microemulsion upon mild agitation following dilution with aqueous phase. This article gives a complete overview of SMEDDS as a promising approach to effectively tackle the problem of poorly soluble molecules.